Comparison of Ultrasound-Guided Ankle Block Versus Anatomical Landmark-Guided Ankle Block in Ankle and Foot Surgery Under Regional Anesthesia - Muhammad Javed Khan, Abdullah Babar, Imran Ul Haq, Roheena Wadud, Khayyam Farid, Abdul Waheed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: As more patients undergo foot and ankle surgery, regional anesthesia's significance in postoperative treatment has grown. Anesthesiologists and pain specialists have adopted regional anesthesia in large numbers. Numerous techniques, such as nerve stimulation, anatomical markers, and ultrasonography, have been used to block the saphenous nerve. Objective: The present study aimed to assess the traditional anatomic landmark-guided approaches in lower limb surgery performed under regional anesthesia with ultrasound-guided ankle blocks in surgical anesthetic methods. Method: This randomized control study is carried out at the hospital. A total of 60 participants with scheduled foot and ankle surgery were randomly divided into two study groups (each n=30), Ultrasound-guided ankle block (USG) and anatomical landmark-guided ankle block (ALG). Results: Recruited participants had a mean age of 50.2± 14.02, with 39 (65%) male and 21( 35%) female. A total of 49 patients (82%) were able to undergo anesthesia successfully, with 26 (86.60%) of those patients belonging to the USG block group and 23 (76.60%) of those patients belonging to the ALG block group undergoing anesthesia successfully (p-value = >0.999). Practical implication: This study will help to comprehend either ultrasound-guided ankle block or anatomical landmark-guided ankle block in foot surgeries give better results. Conclusion: The results of this research indicate that the success rates of the two procedures are statistically insignificantly different; however, the USG ankle block for surgical anesthesia performed under regional anesthetic had a greater success rate than the anatomic landmark-guided technique. Keywords: Foot surgery, USG ankle block, anesthesia, ALG Block, postoperative treatment